OPTIMIZATION OF HOLIATRY TREATMENT OF ACUTE INTESTINAL INFECTIONS: APPROACH WITH PROBIOTIC LACTO AND ORAL SOLUTION REO - Сидорчук, Анюта; Венгловская, Ядвига; Грубляк, Людмила; Богачик, Нонна (SWorldJournal, 2021)
The article dedicated to the study of efficiency application of contemporary probiotic "Lacto" in the combination with oral solution Reo in the holiatry treatment of patients with acute intestinal infections. Clinical and microbiological efficiency of lac